Implementation of Didactical Design on Circle Material at Junior High School - Nopriana, Tri; Rosita, Cita Dwi; Halbi, Diana (Kreano, Jurnal Matematika Kreatif-Inovatif, 2022)
This study aimed to implement a didactic situation design to overcome learning obstacles in the circumference and area of the circle. The method used is qualitative research with Didactical Design Research which goes through the last two stages, namely metapedadidactic analysis and retrospective analysis. The instrument used is a didactic situation design prepared by Rosita, Maharani, Tonah Munfi (2020) and interview guidelines. Based on the implementation results, the didactic situation that has been designed has not been able to overcome students' learning obstacles fully. In addition, a new learning obstacle appears in the concept of the circumference of a circle. Not all students can measure the length of the curvature of a circle because there are inaccurate measurement results. In this study, the didactic design was revised regarding the circumference and area of a circle based on metapedadidactic and retrospective analysis.Penelitian ini bertujuan untuk mengimplementasikan rancangan situasi didaktis sebagai upaya mengatasi learning obstacle pada materi keliling dan luas lingkaran. Metode yang digunakan adalah penelitian kualitatif dengan Didactical Design Research yang melalui dua tahap terakhir yaitu analisis metapedadidaktik dan analisis retrospektif. Instrumen yang digunakan berupa rancangan situasi didaktis yang telah disusun oleh Rosita, Maharani, Tonah Munfi (2020) serta pedoman wawancara. Berdasarkan hasil implementasi, situasi didaktis yang telah dirancang belum sepenuhnya dapat mengatasi learning obstacle siswa. Selain itu, terdapat learning obstacle baru yang muncul pada konsep keliling lingkaran yaitu tidak semua siswa mampu mengukur panjang lengkungan lingkaran karena terdapat hasil pengukuran yang kurang akurat.Pada penelitian ini, dilakukan perbaikan kembali desain didaktis mengenai konsep keliling dan luas lingkaran yang disusun berdasarkan analisis metapedadidaktik dan retrospektif.